Cross–compliance – statutory management requirements (Situation of the Czech Republic) - Michaela BUDŇÁKOVÁ; Pavel ČERMÁK; Jaroslav STAŇA (Acta Agriculturae Slovenica, 2006)
Common Agricultural Policy of EU means to transform the system of farm subsidies in the European Union. The conditions of direct payments in the frame of the new system under the common agriculture policy reform are called “single payment scheme“(SPS). Statutory management requirements and rules of good agricultural and environmental conditions are called collectively as cross-compliance. Since January 1, 2009 complying with the system of complete cross-compliance rules will be the condition for claiming direct payments also in the Czech Republic. The system of cross-compliance will be applied not only in the case of direct payments, but also in the case of subsidies from European Agricultural Fund for Rural Development.